Arab Republic of Egypt : World Bank. (World Bank, 2003)
This is a joint report of the National Council for Woman (NCW), Government of the Arab Republic of Egypt, and the World Bank. Its audience is policy makers and advisors on gender issues in the government, donor community, as well as civil society at large, The report is the first output from an ongoing process to devise a gender main streaming strategy for Egypt.